Efek Aplikasi Periode Kekeringan Dan Macam Pupuk Kandang Terhadap Tanaman Padi - Adi Oksifa Rahma Harti; Syafrullah Salman; Acep Atma Wijaya; Euis Ratanasari (AGRIVET JOURNAL, 2020)
Manure which is applied into the soil has a role to assist the soil in storing water as water supply for plant life by maintaining the structure to become more crumb. . The purpose of this study was to evaluate the combination of treatments between types of manure and the period of drought on the growth and yield of rice plants (Oryza sativa L.). The study was conducted at the home of Sumedang Regency in,  design used a randomized randomized block design (RBD) with 32 combinations of treatments namely a combination of A = No manure + initial period of 4 mst drought, B = No manure + initial period of drought 7 mst, C = without manure + initial period of drought 10 mst, D = cow manure + initial period of drought 4 mst, E = cow manure + initial period of drought 7 mst, F = cow manure + initial period drought 10 mst, G = goat manure + initial drought period 4 mst, H = goat manure + initial drought period 7 mst, I = goat manure + initial drought period 10 mst, J = chicken manure + initial drought period 4 mst, K = chicken manure + initial period of drought 7 mst, L = chicken manure + initial period of drought 10 mst. While the Combination H Treatment has a good effect on plant height, E combination has a good effect on the number of tillers, does not show a real effect on root length and root distribution, but shows a real effect on root volume, which is the best combination of treatments with 7 and 10 MST, combination treatment with 10 MST has a very good effect on the number of productive tillers, number of grain per clump, number of empty grains per clump, grain weight per clump and weight of 1000 grains. Combination of treatment with 4 mst died.